Editorial. Issue 1 (1st March 2016) - Edney, Kathryn; MacDonald, Laura
This editorial provides an overview of, and the history behind, the special issue of Studies in Musical Theatre entitled 'All Kinds of Music is Pouring Out of Me: Living Large and Feeling Big in Musical Theatre Performance and Reception'.